2012
DOI: 10.1111/j.1532-7795.2012.00815.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Work and Alcohol Use Revisited: Variations by Family Structure

Abstract: Previous research finds adolescent work hours to be associated with increased alcohol use. Most studies, however, fail to account for possible selection effects that lead youth to both work and substance use. Using data from the first two waves of the National Longitudinal Study of Adolescent Health (N = 12,620), a fixed effects regression method is employed to control for stable between-person differences neglected by previous studies. Results show little relationship between work hours and alcohol use when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Although there were no significant differences by social class, the effects of moderate and intense work on binge drinking were significantly greater among those from relatively advantaged neighborhoods. That the relationships between work intensity and binge drinking are stronger among those from advantaged backgrounds is consistent with previous studies that have considered family structure as an indicator of disadvantage (Bachman et al 2013;Rocheleau and Swisher 2012).…”
Section: Multivariate Moderation Modelssupporting
confidence: 91%
See 4 more Smart Citations
“…Although there were no significant differences by social class, the effects of moderate and intense work on binge drinking were significantly greater among those from relatively advantaged neighborhoods. That the relationships between work intensity and binge drinking are stronger among those from advantaged backgrounds is consistent with previous studies that have considered family structure as an indicator of disadvantage (Bachman et al 2013;Rocheleau and Swisher 2012).…”
Section: Multivariate Moderation Modelssupporting
confidence: 91%
“…Some previous research supports this idea, finding that the positive relationship between adolescent work and delinquency is limited to those from more advantaged backgrounds (Bachman et al 2013;Bauermeister et al 2007;Breslin and Adlaf 2005;Johnson 2004;Rocheleau and Swisher 2012). Focusing on family structure, Rocheleau and Swisher (2012) found that the positive relationship between work and drinking was stronger for adolescents residing in twobiological-parent households, whereas a negative association was observed among youth from singleparent households (see also Bachman et al 2013). With respect to racial and ethnic differences, Johnson (2004) found a positive relationship between work and substance use among white adolescents, but no consistent relationship among minority adolescents.…”
Section: Adolescent Work Social Class and Neighborhood Disadvantagementioning
confidence: 88%
See 3 more Smart Citations